(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
A body is said to be in a state of plane deformation, if the displacements of the points of the body are parallel to one plane and do not depend on the coordinate in the direction perpendicular to the plane (of the points). If the 0xy plane is taken as the deformation plane, then